Assessment of the abdominal wall function after pedicled TRAM flap surgery for breast reconstruction: Use of modified mesh repair for the donor defect - Sharma, RameshKumar; Singh, Gurpreet; Cyriac, Chacko (Indian journal of plastic surgery, 2010)
The pedicled TRAM flap has been a workhorse of autologous breast reconstruction for decades. However, there has been a rising concern about the abdominal wall donor site morbidity with the use of conventional TRAM flap. This has generally been cited as one of the main reasons for resorting to "abdominal wall friendly" techniques. This study has been undertaken to assess the abdominal wall function in patients with pedicled TRAM flap breast reconstruction. The entire width of the muscle and the overlying wide disk of anterior rectus sheath were harvested with the TRAM flap in all our patients and the anterior rectus sheath defect was repaired by a Proline mesh. Abdominal wall function was studied in 21 patients who underwent simultaneous primary unipedicled TRAM flap reconstruction after mastectomy for cancer. In all the patients, the abdominal wall defect was repaired using wide sheet of Proline mesh both as inlay and onlay. The assessment tools included straight and rotational curl ups and a subjective questionnaire. The abdominal wall was also examined for any asymmetry, bulge, or hernia. The minimal follow-up was 6 months postoperative. The objective results were compared with normal unoperated volunteers. The harvesting the TRAM flap certainly results in changes to the anterior abdominal wall that can express themselves to a variable degree. A relatively high incidence of asymptomatic asymmetry of the abdomen was seen. There was total absence of hernia in our series even after a mean follow-up period of 15.5 months. A few patients were only able to partially initiate the sit up movement and suffered an important loss of strength. In most patients, synergists took over the functional movement but as the load increased, flexion and rotation performances decreased. The lack of correlation between exercise tests and the results of the questionnaire suggests that this statistically significant impairment was functionally not important. The patients encountered little or no difficulty in theis day-to-day activities. Our modification of use of a wide mesh as inlay and onlay repair minimizes the donor site morbidity. This also avoids maneuvers meant for primary closure of the rectus sheath defects, which can result in distortion of umbilicus. Therefore, in conclusion, the unipedicled TRAM flap should be regarded as a valuable option in breast reconstruction provided careful repair of the abdominal wall defect is undertaken using Proline mesh.